MOTIVATIONS FOR ACTIVISM: EXPLORING BERSIH ACTIVISTS’ COMMUNICATIVE ECOLOGIES - Ngu, Ik Ying (2024)
Social media provides people with new ways of approaching and engaging in politics. This article explores how Bersih activists develop new communicative practices and motivations for their activism. The study investigates the communicative strategies that they employed in using social media to mobilise their supporters and explores their personal communicative experiences, which are likely to enhance their public commitment. This study draws on data collected from a longitudinal study conducted before and after the 14th General Election (GE14) in 2018, which saw the fall of the dominant Barisan Nasional (BN) coalition after ruling continuously for six decades. Findings show Bersih activism uses mediated and unmediated communication strategies in mobilisation, each of which is organised in a particular way that connects activists with their local and global networks. This study concludes that motivation moderates the three layers of activists’ communicative ecology and the integration of social media into their everyday life helps to actualise collective affordances. Bersih activists use social media to deliver truthful information about their activism as this helps to combat the distribution of fake news, and reinforce the political participation that helps to sustain Malaysian democracy.